Investigation of the effects of lean mixtures on combustion and particulate emissions in a DISI engine fueled with bioethanol-gasoline blends. (15th January 2020) - Zhao, Lifeng; Wang, Xueyuan; Wang, Defu; Su, Xiangyang
Abstract: Ethanol, an oxygen-containing biofuel, is a promising alternative fuel for SI engines. Ethanol/gasoline blends with <10% volume ratio are available approaches to minimize life-cycle greenhouse gas emissions, ethanol addition as high as 21% vol. is potentially used duce to anti-knock performance, improvement to thermal efficiency and greenhouse gas emissions. The ethanol/gasoline blend E20 was investigated in this study in terms of particle emissions reduction and engine efficiency. The combustion, particle number (PN) concentration, and particle size distribution of a turbo-charged GDI engine fueled with E20 were investigated under both stoichiometric and lean burn conditions. The particle size distribution was measured in excess air ratio and injection timing. The results show that the combustion efficiency of E20 fuel increased under lean burn conditions – up to an excess air coefficient of 1.2 – 1.3 – and the fuel consumption rate was 5% lower than the gasoline consumption rate under stoichiometric conditions. The PN emissions of nucleation and accumulation particles during lean burn were also markedly reduced. The lowest PN emissions were observed in the leanest mixture (excess air ratio 1.3), and the averaged size of particles decreased as the lean mixture increased resulting in a significant reduction in particle surface area concentration. The PN emissions decreased with retarded injection timing in the early intake stroke as accumulation particles decreased significantly. The total particle quantity increased as the fuel was injected in the late intake stroke and PN (>20 nm) quantity increased as the injection timing was retarded to 240°CA BTDC.